Inflammation: the driver of poor outcomes among children with severe acute malnutrition? - Sturgeon, JP; Njunge, JM; Bourke, CD; Gonzales, GB; Robertson, RC; Bwakura-Dangarembizi, M; Berkley, JA; Kelly, P; Prendergast, AJ (Oxford University Press, 2023)
Severe acute malnutrition (SAM) is the most life-threatening form of undernutrition and underlies at least 10% of all deaths among children younger than 5 years in low-income countries. SAM is a complex, multisystem disease, with physiological perturbations observed in conjunction with the loss of lean mass, including structural and functional changes in many organ systems. Despite the high mortality burden, predominantly due to infections, the underlying pathogenic pathways remain poorly understood. Intestinal and systemic inflammation is heightened in children with SAM. Chronic inflammation and its consequent immunomodulation may explain the increased morbidity and mortality from infections in children with SAM, both during hospitalization and in the longer term after discharge. Recognition of the role of inflammation in SAM is critical in considering new therapeutic targets in this disease, which has not seen a transformational approach to treatment for several decades. This review highlights the central role of inflammation in the wide-ranging pathophysiology of SAM, as well as identifying potential interventions that have biological plausibility based on evidence from other inflammatory syndromes.